Analisis Kinerja Keuangan pada Rasio Aktivitas dan Rasio Likuiditas Terhadap Perusahaan Radiant Utama Interinsco Tbk Tahun 2016-2020 - Dwi Budi Srisulistiowati; Sri Rejeki (J-MAS (Jurnal Manajemen dan Sains), 2022)
Ratio analysis is a method used to analyze a company's financial statements. The purpose of this study is to determine the performance of financial statements by analyzing the ratio of activity and liquidity based on those listed on the IDX, namely the financial statements of PT. Radiant Utama Interinsco Tbk 2016-2020. This study uses a descriptive type of research with a quantitative approach. In this case, the report used to analyze the financial statements of PT Radiant Utama Interinsco Tbk. By reviewing financial reports, performing calculations, comparing or measuring, and applying reporting results from research. The technique used consists of the use of reports related to the analysis of activity ratios and liquidity ratios. Based on the calculation results of the table above, it can be concluded that the ratio of Current Assets of PT Radiant Utama Interinsco Tbk from 2016 to 2020 has an unstable value. Because in 2016 to 2017 it decreased, while in 2018 to 2019 it increased and again decreased in 2020. It can be seen in the current ratio of PT Radiant Utama Interinsco Tbk which is not satisfactory because it is still below the industry average value. Suggestions in this study is that PT Radiant Utama Interinsco Tbk needs to evaluate management performance, whether it runs effectively or not. In addition, it is also necessary to re-evaluate the use of its assets, to be able to measure the level of efficiency in the use of company resources. Because seen from the ratio of Working capital turn over and Fixed assets turn over PT Radiant Utama Interinsco Tbk continues to decline from year to year. In this case the management must work harder to increase the effectiveness and efficiency of its assets.